Ecological network construction and community resilience analysis of nocturnal birds: a case study of Hangzhou City, Zhejiang Province, China - Yang Jin; Mingkan Zhang; Danying Yan; Kun Li; Chao Zhou; Xi Chen (Ecological Indicators)
Constructing nocturnal ecological networks at the municipal scale is crucial for conserving nocturnal biodiversity and promoting regional ecological sustainability. In this study, focusing on nocturnal birds (Strigiformes) in Hangzhou City as an example, from temporal and spatial dimension to integrate environmental variables in order to identify nocturnal ecological network. Using community detection methods to analyze the differences in attributes, habitats, and topological structures between network communities. In order to analyze the impact of communities on network resilience, four network optimization strategies were developed to simulate different scenarios. From transient and continuous impact perspectives, using the Maximum Connected graph and Global Efficiency to measure network resilience. The study identified 133 ecological sources, 378 ecological corridors, and 5 communities. The priority protection community is located in the centre urban. Enhancing internal-community connectivity is more suitable to protect against transient attacks, while enhancing external-community connectivity is more effective to protect against cascading failures. The choice of dominant and subordinate communities also has a significant impact on network resilience. These findings provide important insights for building and optimizing dark infrastructure, and make substantial contributions to preserving nocturnal biodiversity and enhancing urban sustainability.